Associations of Specific Types of Fruit and Vegetables with Perceived Stress in Adults: The AusDiab Study. (14th June 2022) - Bagatini, Simone Radavelli; Sim, Marc; Blekkenhorst, Lauren; Bondonno, Nicola; Bondonno, Catherine; Woodman, Richard; Dickson, Joanne; Magliano, Dianna; Shaw, Jonathan; Daly, Robin; Hodgson, Jonathan; Lewis, Joshua
Abstract: Objectives: Prolonged exposure to stress is a risk factor for mental and physical health problems (i.e., depression, cardiovascular disease). Although higher consumption of fruit and vegetables (FV) has been associated with lower perceived stress (PS), the relationship between specific FV types and PS remains uncertain. The aim of this cross-sectional study was to explore the relationship between consumption of specific FV types with PS in a cohort of men and women aged 25–92 years who took part in the Australian Diabetes, Obesity and Lifestyle (AusDiab) Study. Methods: A validated Food Frequency Questionnaire was used to assess dietary intake (n = 8, 640). A validated questionnaire was used to assess PS (high PS cut-offs were obtained from the highest quartile of PS for each sex). Multivariable-adjusted logistic regression was performed to investigate the associations. Results: The mean age of participants (50.1% females) was 47.8 (SD 15) years. Those in the highest quartiles of apples and pears, orange and other citrus, and banana intakes had a significantly lower odds (24–31%) of having high PS, compared to lowest. Similarly, those with higher intakes of cruciferous, yellow/orange/red, and legume vegetables had significantly lower odds (25–27%) of having high PS. Conclusions: In Australian adults, a higher consumption of different types of FV may alleviate stress and potentially improve mental and physical wellbeing. Funding Sources: This study received no specific grant from any funding agency in the public, commercial or not-for-profit sectors. The salary of MS and CPB is supported by a Royal Perth Hospital Research Foundation Career Advancement Fellowship. The salary of LCB is supported by a National Health and Medical Research Council (NHMRC) of Australia Emerging Leadership Investigator Grant and a National Heart Foundation of Australia Post-Doctoral Research Fellowship. The salary of JRL is supported by a National Heart Foundation of Australia Future Leader Fellowship. The salary of JMH is supported by a National Health and Medical Research Council of Australia Senior Research Fellowship. The salary of JES is supported by a National Health and Medical Research Council Investigator Grant. None of the funding agencies had any role in any aspects of the manuscript.